2019
DOI: 10.5603/kp.a2018.0241
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic exercise testing in adults: performance and interpretation. An expert opinion of the Polish Cardiac Society Working Group on Cardiac Rehabilitation and Exercise Physiology

Abstract: A b s t r a c tElectrocardiographic (ECG) exercise stress test has been a major diagnostic test in cardiology for several decades. Ongoing technological advances that have led to a wide use of imaging techniques and development of new guidelines have called for a revised and updated approach to the technique and interpretation of the ECG exercise testing. The present document outlines an expert opinion of the Polish Cardiac Society Working Group on Cardiac Rehabilitation and Exercise Physiology regarding the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Furthermore, specific recommendations in the guidelines of the European Society of Cardiology on cardiac pacing and cardiac resynchronization therapy are limited [2,3]. Many studies rely on the electrocardiographic treadmill exercise test as an objective method of assessment of physical performance and progress in cardiac rehabilitation or for optimization of settings of implantable devices and cardiac [7,12,13]. Therefore, this study will deepen the research on the impact of the rate response function on physical performance in a homogeneous group of patients and will reveal which patients would benefit the most from rate-adapted pacing.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, specific recommendations in the guidelines of the European Society of Cardiology on cardiac pacing and cardiac resynchronization therapy are limited [2,3]. Many studies rely on the electrocardiographic treadmill exercise test as an objective method of assessment of physical performance and progress in cardiac rehabilitation or for optimization of settings of implantable devices and cardiac [7,12,13]. Therefore, this study will deepen the research on the impact of the rate response function on physical performance in a homogeneous group of patients and will reveal which patients would benefit the most from rate-adapted pacing.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have found that this stratification is not often done by reque-sting doctors, resulting in many inappropriate ETTs and consequently, increased expenditure [4,5,9]. In order to minimize false negatives/positives, ETTs are recommended for individuals with an intermediate pretest probability [4,6,9,10]. It is not recommended that asymptomatic, very low or low risk patients be made to undergo this test [9].…”
Section: Discussionmentioning
confidence: 99%
“…The ETT is a useful, non-invasive test that is relatively cost effective [4,5]. Its use in diagnosis and prognostication requires that the test be done by a skilled individual [6] in order to maximise its rather low sensitivity of 67% [3,4]. Accurate interpretation is not solely dependent on ST segment changes during exercise, but other parameters like the presence of chest pain, heart rate at onset of symptoms (if any) and workload done at the end of the test [4,7,8].…”
mentioning
confidence: 99%
“…The exercise test is used to determine exercise intensity, exercise-related risk, as well as changes in exercise capacity after completing each phase of CR. It is also applied to determine workload for subsequent physical activity associated with work and leisure [16];…”
Section: Determining Patient Eligibility For Comprehensive Cardiac Rehabilitation: General Principlesmentioning
confidence: 99%